Janneta procedure fot TN patients . Clinical symptoms and surgical outcomes of our patients over 2 years - محفوض مفيد (Latakia University Journal -Medical Sciences Series, 2021)
Trigeminal neuralgia (TN) is a disorder characterized by recurrent unilateral brief, electric, shock-like pains, abrupt in onset and termination, limited to the distribution of one or more divisions of the trigeminal nerve, often triggered by innocuous trigeminal tactile stimuli. One of the earliest known descriptions of paroxysmal facial pain was by the Arab physician Jurjani in the 11th century. He described “a type of pain which affects the teeth on one side and the whole of the jaw on the side which is painful. The diagnosis is made on the history alone, based on characteristic features of the pain. We reviewed 14 patients who came to our clinic between 2017-2019 and followed them up to 2 years. WE divided them depend on their clinical symptoms to group A (Typical TN) and group B (Atypical TN) The outcomes were great. Vas Score decreased with statistically significant and PGIC were better in more than 60 % in group B and 100% in group A. The fist-line treatment for TN is medical or pharmacologic but we conclude that early surgery should be in our first options because it has better outcomes than others treatments.